Diagnosis of land degradation and analysis of its spatiotemporal evolution in the Jinghe River Basin, Xinjiang - Ya Peng; Zhaopeng Wu; Xinpeng Shi; Yuting Tian; Ruirui Zhang (Ecological Indicators)
Land degradation is one of the serious environmental problems faced globally, with profound impacts on human society, ecosystems, and economic development. The situation and trend of land degradation in the Jinghe River Basin are not clear. This study constructs a comprehensive Land Degradation Index (LDI) through multiple indicators to analyze the trend of land degradation in the Jinghe River Basin. The results show that from 2000 to 2020, the area of land degradation in Jinghe County is gradually decreasing, with severe land degradation decreasing annually and mild land degradation increasing annually. During the study period, moderate and above land degradation in Jinghe County was concentrated in the central part, and its center of gravity moved spatially from the northwest to the southeast, and then to the southwest, generally showing a “V” shape; the overall state of land degradation is relatively stable. Single land degradation process types account for 19.24 % of the total land degradation area and compound land degradation accounts for 80.76 %. In general, the type of land degradation in Jinghe County over the 20 years is still mainly compound land degradation. Land degradation in Jinghe County is formed by the combined action of nature and human social activities. Human activities are the leading factor in the increase of LDI, but natural factors have a significant correlation with local LDI changes; temperature, Normalized Difference Vegetation Index (NDVI), and population have a higher impact on the LDI changes in Jinghe County, and local LDI changes respond more strongly to precipitation, evapotranspiration, and Gross Domestic Product (GDP). The research results are of great significance for the management of land use and the promotion of ecological protection in Jinghe County.